2013
DOI: 10.1371/journal.pone.0077139
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Functional Gene Microarray to Probe the Functional Ecology of Ammonia Oxidation in Nitrifying Activated Sludge

Abstract: We report on the first study trialling a newly-developed, functional gene microarray (FGA) for characterising bacterial and archaeal ammonia oxidisers in activated sludge. Mixed liquor (ML) and media biofilm samples from a full-scale integrated fixed-film activated sludge (IFAS) plant were analysed with the FGA to profile the diversity and relative abundance of ammonia-oxidising archaea and bacteria (AOA and AOB respectively). FGA analyses of AOA and AOB communities revealed ubiquitous distribution of AOA acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…1). A functional gene array (FGA) is an ideal approach because it allows an efficient and targeted search for N-cycling microbes [9]. Because FGAs are a rapid and cost-effective method for detecting microbes and their functional genes from virtually any sample, they can be applied to a wide array of sample types [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1). A functional gene array (FGA) is an ideal approach because it allows an efficient and targeted search for N-cycling microbes [9]. Because FGAs are a rapid and cost-effective method for detecting microbes and their functional genes from virtually any sample, they can be applied to a wide array of sample types [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A functional gene array (FGA) is an ideal approach because it allows an efficient and targeted search for N-cycling microbes [9]. Because FGAs are a rapid and cost-effective method for detecting microbes and their functional genes from virtually any sample, they can be applied to a wide array of sample types [9,10]. For example, FGA studies investigating nitrogen cycling associated with harmful cyanobacterial and dinoflagellate blooms in freshwater and marine environments showed that genes and bacteria driving N cycling were spatially and temporally dynamic [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations